1986 Agricultural Research, Southeast Kansas Branch Station - L. W. Lomas; K. W. Kelley; G. M. Paulsen; J. L. Moyer; D. W. Sweeney (Kansas Agricultural Experiment Station Research Reports, 1986)
Research on crops, beef cattle, and related topics at the Southeast Kansas Branch Station.
Keywords: beef cattle; forage; wheat; soybeans; alfalfa; sunflower; fescue; weeds; grain sorghum; soil; water management